IMPLEMENTASI ALGORITMA K-MEANS UNTUK PENGELOMPOKAN PENYAKIT PADA PUSKESMAS BUKIT KAYU KAPUR - Rubiati, Nur; Kurniawan, Rahmad; Hidayatullah, Rahmat; Ridarmin, Ridarmin; Adrianto, Sukri; Yunita, Putri; Pratiwi, Fitri; Arianto, Adi; Widodo, Pulla Pandika; Mardayulis, Mardayulis; Abnita, Suci Nur (I N F O R M A T I K A, 2023)
Along with the increasing number of patients at Bukit Kayu Kapur Public Health Center, there is a need for data collection and analysis of these patient data. The analysis that needs to be considered is regarding the grouping of acute and chronic diseases. The grouping can be done using the K-Means method. To make the analysis process easier, the K-Means method can be implemented into a system. Making this system using Flutter and Web-based. The design of this system is divided into use case diagrams, activity diagrams, flowcharts, and data modeling. The results of implementation and testing show that the system has been functioning properly. The system created can be used to group data easily with easy-to-understand data visualizations.